The Main Character's Oppression in Abi Dare’s The Girl with Louding Voice - Ardiansyah, Muhammad Yudi (Journal of Literature, Linguistics, & Cultural Studies, 2022)
Oppression often occurs in the community. It can be due to poverty or existing habits. One of the novels by Abi Dare entitled The Girl with Louding Voice was one of the novels talking about the oppression received by the main character (Adunni). The novel was the main data source in this research. The aims of the study were to find out what oppression Adunni was experiencing as the main character and to explain Adunni's struggles to get out of this oppression. The researcher used a feminist critique approach with textual studies to analyze the data and apply Young’s oppression and Lerner's feminism theory. The oppression includes powerlessness, cultural imperialism, marginalization, violence, and exploitation. Adunni experienced all those things. It resulted in her having to stop her education, marrying forcibly, getting abused and being defrauded and having many wounds all over her body. However, she never gave up because she had determination and big dreams. She believed that continuing her education to the highest level would free her from oppression. Therefore, she made several efforts, such as persuading her father, asking for help, studying and teaching, running away from home, giving resistance, avoiding certain people, refusing to get pregnant, and participating in the selection of a scholarship.